Effects of Eight-Week Single-Set Resistance Training on Muscle Health, Metabolic Profile and Oxidative Stress in Individuals with Cognitive Impairment - Mariana Lopes; Mário C. Marques; Nuno Fonseca; Diogo L. Marques; Célia Nunes; Daniel A. Marinho; Henrique P. Neiva; Mikel Izquierdo; Dulce Esteves; Carla P. Fonseca (Applied Sciences, 2025)
Resistance training (RT) has emerged as an effective strategy to counteract the deleterious effects of aging, improving metabolic health, and preserving functional capacity. However, the impact of low-volume RT on older adults, particularly those with cognitive impairment, remains underexplored. This study investigated the effects of an eight-week low-volume RT program on muscle health, liver function, lipid profile, glycemic control, and oxidative stress markers in individuals with cognitive decline. Twenty-eight participants were assigned to a low-volume RT group (81.0 ± 9.66) and a control group (90.0 ± 10.39 years). The low-volume RT group performed an 8-week RT program (two sessions per week) comprised of one set of 6–12 repetitions at 40–70% 1RM. The control group did not receive the intervention. Before and after the 8 weeks, the biomarkers of muscle health, metabolic profile, and oxidative stress were assessed. The results showed no significant differences between the groups in any biomarker at the baseline or post-test. The intervention group showed a significant increase in serum lactate dehydrogenase, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) activities, all of which remained within normal ranges. No changes were observed in serum creatine kinase activity or the AST/ALT ratio in the intervention group, suggesting that acute-phase responses were occurring rather than tissue damage. Additionally, the intervention group showed a significant increase in high-density lipoprotein cholesterol levels, accompanied by a reduction in the atherogenic index, indicating potential cardiovascular benefits. No significant alterations were detected in the glycemic control and lipid peroxidation markers. These results suggest that low-volume RT can elicit modest, yet clinically meaningful metabolic improvements in individuals with cognitive impairment. Future studies should focus on identifying the minimal effective RT dose needed to optimize the health benefits in this vulnerable population, facilitating long-term adherence to exercise interventions.